ANALISIS PENGARUH BANK SIZE, LDR, BOPO, PERTUMBUHAN KREDIT, DAN CAR TERHADAP NON PERFORMING LOAN (Studi Kasus Pada Bank Umum Konvensional yang Terdaftar di BEI Tahun 2010-2014) - Ad'hadini, Nadya Dwi; Kusumawardhani, Amie (Faculty of Economics and Business Diponegoro University, 2016)
This research aims to analyze the influence of bank size, loan to deposit ratio (LDR), bank inefficiency, credit growth, and capital adequacy ratio (CAR) to credit risk that measured by non performing loan (NPL). Case study on conventional commercial banks listed on Indonesia Stock Exchange (IDX) in 2010-2014. The number of sample used in this research were 30 banks. The data used were obtained from financial statements and banking annual report published by Indonesia Stock Exchange in 2010-2014. The analytical method used in this research is Multiple Linear Regression Analysis where previously performed classical assumption that includes Normality Test, Multicollinearity Test, Autocorrelation Test, and Heteroskedastisitas Test. Based on the results of tests performed, bank size, loan to deposit ratio (LDR), bank efficiency, credit growth, and capital adequacy ratio (CAR) have significant effect on non-performing loans (NPL). Bank size, loan to deposit ratio (LDR), bank inefficiency, and credit growth have positive impact on non-performing loans (NPL). While capital adequacy ratio (CAR) have negative but not significant impact on non-performing loans (NPL). Based on the coefficient determination R2, variable bank size, loan to deposit ratio (LDR), bank inefficiency, credit growth, and capital adequacy ratio (CAR) have 44.2% effect against non-performing loans (NPL). While the remaining 55.8% is influenced by other variables that are not used in this study.An increase in non-performing loans can lead a bank to experience bankruptcy so disrupting economic activity. With the result that mentioned above means the control of the bank internal factors will affect the level of non-performing loans. The results of this study are expected to help banks manage internal factors mainly as bank size, LDR, bank inefficiency, and credit growth must be monitored continuously when increased so as to prevent any non-performing loans.